Biomass production and chlorophyll contents of cover crops in compacted soils (Research, Society and Development, 2023)
Soil compaction is one of the obstacles to grain production in the cerrado, and may influence biomass production and physiological changes, such as chlorophyll production, in cover crops used to minimize compaction damage and soil protection. Thus, the objective was to evaluate the effect of soil compaction on the production of biomass and chlorophyll a, b and total contents of cover crops. The experiment was carried out in a greenhouse at the University of Rio Verde. The treatments were established by a 4 x 2 factorial scheme, being Urochloa ruziziensis, Panicum maximum – BRS zuri, maize intercropped with U. ruziziensis and single maize, cultivated in soil with and without compaction. Soil compaction reduced the biomass of all cover crops. Maize alone and intercropped with U. ruziziensis grown in soil without compaction provided the soil with a greater amount of surface biomass (shoot and total dry mass), while maize intercropped with U. ruziziensis in compacted soil provided greater dry mass of roots. Comparing the contents of chlorophyll a, b and total within the same species, it is observed that there was no increase in the chlorophyll content in terms of soil compaction. Therefore, it is concluded that soil compaction impairs the development of biomass, but does not change the chlorophyll content of cover crops.